PENGARUH LOYALITAS DAN KOMITMEN TERHADAP PENGHARGAAN NASABAH PADA BANK BJB KCP CIKAMPEK - Uus Md Fadli; Ummul Azizah (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2023)
Service procedures in marketing have a very important role for a company. By using a marketing strategy, a company will be able to develop, earn profits, and be able to maximize product sales volume and be able to maintain customer loyalty to the bank. This study aims to determine service procedures in increasing customer loyalty at Bank BJB KCP Cikampek. This study used an implementative descriptive method, namely interviews, observations, and literature or document studies. There are 2 sources of data used, namely primary data and secondary data. Primary data was obtained directly and secondary data was obtained through literature and other references. The results showed that the higher customer satisfaction, the higher customer loyalty. Bank BJB in creating customer loyalty gets the most satisfied answers from the statements of trusted bank employees.